2007
DOI: 10.5194/angeo-25-399-2007
|View full text |Cite
|
Sign up to set email alerts
|

MLT gravity wave climatology in the South America equatorial region observed by airglow imager

Abstract: Abstract. An all-sky CCD imager for OH, O 2 and OI (557.7 nm) airglow emission measurements was operated at São João do Cariri (Cariri), Brazil (7 • S, 36 • W), from October 2000 to December 2004. A large amount of image data, more than 3000 h of observation and around 1000 wave events, makes it possible to classify the gravity wave characteristics, which are statistically significant. The observed waves show a typically short horizontal wavelength (5-45 km) and a short period (5-35 min), and horizontal phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…8e is found to be 190 m/s which is much larger than maximum GW amplitude (of order of 43 m/s) considered by Kherani et al (2009). In the work of Kherani et al (2009), the GW with maximum amplitude equals to 43 m/s, was considered to explain the plasma bubble activity during October equinox month which is the season of minimum GW activity as found by Medeiros et al (2007). During December summer month, GW activity is found to be maximum and this is the reason for considering large GW amplitude (almost four times larger than October month) in present study.…”
Section: Numerical Simulation Of CII Under Ionospheric Conditions Cormentioning
confidence: 97%
See 1 more Smart Citation
“…8e is found to be 190 m/s which is much larger than maximum GW amplitude (of order of 43 m/s) considered by Kherani et al (2009). In the work of Kherani et al (2009), the GW with maximum amplitude equals to 43 m/s, was considered to explain the plasma bubble activity during October equinox month which is the season of minimum GW activity as found by Medeiros et al (2007). During December summer month, GW activity is found to be maximum and this is the reason for considering large GW amplitude (almost four times larger than October month) in present study.…”
Section: Numerical Simulation Of CII Under Ionospheric Conditions Cormentioning
confidence: 97%
“…It was also found that the amplitude of GW seeding, to lead to plasma bubble development, becomes crucial for low PRPV. The seasonal variations of GW activity over Brazilian equator-low-latitude region is studied during night-time (Medeiros et al, 2007) and day-time (Aveiro et al, 2009). It is found that both during day and night-time, GW activity peaks in summer (November-February) and Winter (May-August) while remains relatively low during equinoctial months (March-April, September-October).…”
Section: Gravity Wave (Gw) Activity In April and Decembermentioning
confidence: 98%
“…GWs influence the density of reacting species/ambient temperature in the airglow-emitting region, and manifest themselves as the variations in airglow intensity (Noxon, 1978;Hines and Tarasick, 1994). Ground-based observations of different nightglow features from the MLT region have been extensively used in understanding gravity wave phenomenology (Takahashi et al, 1985;Taylor et al, 1995;Isler et al, 1997;Smith et al, 2000;Medeiros et al, 2007;Nielsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This system takes the plasma bubble images by OI 630.0 nm and the gravity wave images by OHNIR with a time integration of typically 90 s for the former and 15 s for the latter. Details of this imager have been reported by Medeiros et al (2007). Fig.…”
Section: Observations and Instrumentationmentioning
confidence: 98%
“…Optical measurements in the MLT (upper mesosphere and lower thermosphere) region frequently observe gravity waves with phase speeds of 20-80 m/s, periods of 5-30 min, and wavelengths of 10-100 km (e.g., Wrasse et al, 2006a;Medeiros et al, 2007). Larger gravity waves (wavelengths longer than a hundred kilometers) have also been studied using the Keogram technique (e.g., Taylor et al, 2009).…”
Section: Introductionmentioning
confidence: 98%